Synthesis, Characterization, and Antibacterial Activity of Dithiophosphonates and Amidodithiophosphonates - Aydemir, Cemal; Solak, Samet; Doganli, Gulumser Acar; Sensoy, Tugba; Arar, Dicle; Bozbeyoglu, Nur; Karakus, Mehmet (Taylor & Francis Ltd, 2015)
New dithiophosphonates [RPS2(OR1)](-) (R-1 = fenchyl and bornyl) and amidodithiophosphonates [RPS2(NHR2)](-) (R-2 = 2-benzyloxycyclohexyl and 1-(4-fluorophenyl)ethyl) have been synthesized by the reaction of (ArPS2)(2) (Ar = p-MeO-C6H4) and (1R)-endo-(+)-fenchyl alcohol and (-)-borneol or the amines (1S,2S)-(+)-2-benzyloxycyclohexylamine and (R)-
Keywords: Staphylococcus-Aureus; Complexes; Ligands; Silver(I); Gold(I)